Cyber hygiene during Covid-19 to avoid cyber attacks - Lee, Yvonne Yi Jin (2022)

(untitled)
This project is a research study on cyber hygiene during COVID-19 to avoid cyber-attacks for academic purposes. Cyber security is crucial in today's cyber defence. Cyber security expenses have increased over the past decade while massive infringements of data and data leaks have also risen. In addition, we need to practice the best cyber hygiene behaviors in order to avoid cyber-attacks like phishing, data loss, and others. Therefore, we need a deeper understanding of how the various variables have an impact on cyber hygiene behaviour. In this study, we will further evaluate how the self-efficacy, cyber hygiene knowledge, and cyber hygiene awareness affect the cyber hygiene attitude and then lead to cyber hygiene behavior. Moreover, the Theory of Planned Behavior (TPB) was used in this study to help investigate the relationship between attitude, intentions, and behavior toward cyber hygiene. Five hypotheses were developed in hopes of identifying the relationship between the factors and cyber hygiene behavior. In order to gain deeper understanding, the questionnaire was created and delivered via the Google Form to the 160 responders. After received the responds from participants, we had run the analysis on all the variables by using SmartPLS 3.3 and calculate the PLS-SEM algorithm of the variables. After running the analysis, we discuss our key findings using the results for each path's t-statistic and p-value. Last but not least, the implications of this study are presented, with the hope that future researchers, policymakers, and practitioners can serve as a reference for further experimental approaches to improve the current state of cyber hygiene behavior.